Penguatan Fungsi Legislasi Produk Hukum Daerah Pada Kabupaten Maluku Tengah dan Seram Bagian Barat - Soplantila, Ronny; Lekipiouw, Sherlock H. L. (Jurnal Locus Penelitian dan Pengabdian, 2025)
The Regional People’s Representative Council (DPRD) is a representative body at the regional level that embodies the principles of democracy as stipulated in Article 18 of the 1945 Constitution. This article states that Indonesia, as a unitary state, is divided into provinces, which are further subdivided into regencies and cities, each of which has its own DPRD. The existence of the DPRD is strategic, as it carries out three main functions: legislation, budgeting, and oversight at the regional level. Regarding the drafting of regional regulations, Article 239 paragraph (1) of Law Number 23 of 2014 on Regional Government stipulates that the planning process is carried out through the regional legislation program (prolegda). Prolegda serves as a planning instrument prepared in a structured, integrated, and systematic manner at both the provincial and regency/city levels. Furthermore, based on Law Number 12 of 2011 on the Establishment of Laws and Regulations, as well as Minister of Home Affairs Regulation Number 120 of 2018 on the Formation of Regional Legal Products, the process of drafting regional regulations includes the stages of planning, preparation, formulation, discussion, approval or enactment, and promulgation. These stages demonstrate that the formation of regional regulations is not merely a formality but must follow the applicable legal mechanisms. As the people’s representatives, DPRD holds the right of initiative in formulating ideas and concepts for regional regulations. This highlights DPRD’s role as the representative of the community who understands the conditions, needs, and aspirations of the people. Therefore, every regional regulation produced is expected to address real issues in society and serve as an effective legal instrument to promote regional welfare and development.